Glioma Contemporary Diagnostic and Therapeutic Approaches - Omerhodžić, Ibrahim; Arnautović, Kenan (IntechOpen, 2019)
The past three decades have been marked with huge enthusiasm from scientists and professionals in an effort to find a cure for glioma disease. Methods to confirm the kinds and grades of glioma have taken a path from classical macro- to microscopic pathohystological confirmation of tumors, through morphological-histological, molecular, and genetic diagnosis. Surgically, progress was made possible with the development and use of technological aids, for example neuronavigation, cortical mapping, electrocorticography, neuromonitoring, functional and intraoperative MRI, magnetoencephalography, etc. Great hope was placed on the extension of tumor resection and popular supratotal resection. Significant progress has been made generally in glioma treatment with the use of modern radiotherapy and new chemotherapeutics. What do we want to see for the future? By way of stem cells, a specific medicine will be produced, individualized for the particular patient, and by using a microcapsule it will be implanted into the brain zone affected by the tumor by way of robot surgery and injection needle. This is not at all an unrealistic expectation in the next decade or two.